Modelling and evaluating software project risks with quantitative analysis techniques in planning software development - Abdelrafe, Elzamly; Burairah, Hussin (University of Zagreb, 2015)
Risk is not always avoidable, but it is controllable. The aim of this paper is to present new techniques which use the stepwise regression analysis to model and evaluate the risks in planning software development and reducing risk with software process improvement. Top ten software risk factors in planning software development phase and thirty control factors were presented to respondents. This study incorporates risk management approach and planning software development to mitigate software project failure. Performed techniques used stepwise regression analysis models to compare the controls to each of the risk planning software development factors, in order to determine and evaluate if they are effective in mitigating the occurrence of each risk planning factor and, finally, to select the optimal model. Also, top ten risk planning software development factors were mitigated by using control factors. The study has been conducted on a group of software project managers. Successful project risk management will greatly improve the probability of project success.